Penentuan Metode Intensitas Hujan Berdasarkan Karakteristik Hujan dari Stasiun Pengamat Hujan Disekitar Kecamatan Karawang Timur - Melisa Permatasari; M. Candra Nugraha; Etih Hartati (Fakultas Teknik, 2020)
The rain intensity is the high rainfall in unit of time. The length of rain will be reversed by the amount rain intensity. The shorter time the rain lasts, the greater of the intensity and re-period of its rain. The value of rain intensity is required to calculate the flood discharge plan on the drainage system planning area in East Karawang district. Determining the value rain intensity is required the maximum daily rainfall data obtained from the main observer stations in the Plawad station planning area. The method of determination rain intensity analysis can be done with three methods: Van Breen, Bell Tanimoto and Hasper der Weduwen. Selected method is based on the smallest deviation value. Determination deviation value is determined by comparing rain intensity value of Van Breen method, Bell Tanimoto, Hasper der Weduwen. By comparing rain intensity value of the Van Breen method, Bell Tanimoto, Hasper der Weduwen with the results of calculating three methods through the method approach Talbot, Sherman and Ishiguro. Calculation results show that the method of rain has smallest deviation standard is method Van Breen with Talbot approach for rainy period (PUH) 2, 5, 10, 25, 50 and 100 years.